Experimental study of the curling effect on austenitic stainless steel bolted connections - Chandra, Louis (Nanyang Technological University, 2022)
An experimental study using 18 specimens of stainless steel bolted connections were conducted to study the effect of out-of-plane deformation on the ultimate strength of stainless steel bolted connections. Each specimen consisted of two austenitic stainless steel plates of different thicknesses and two carbon steel plates. Results from tension tests showed 15 – 57% strength reduction on connections with curling compared to connections without curling. Strength reductions are more prominent on thinner plates or single bolt connections compared to thicker plates or double bolt connections. Comparisons between two design provisions, namely EN1993-1-4 and SEI/ASCE 8-02, showed that both design codes are unconservative and inaccurate in estimating the ultimate strength of stainless steel bolted connections. EN1993-1-4 are found to be relatively better in estimating the ultimate strength and failure modes of the stainless steel bolted connections compared to SEI/ASCE 8-02. Further numerical investigations are necessary to develop new design equations that consider the effect of curling on the design resistance.